Kajian Geologi Teknik dan Potensi Longsor pada Segmen IG1 dan IG2 Akses Tambang di Kabupaten Pohuwato, Gorontalo - Immanuel Ginting; Aang Panji Permana; Ahmad Zainuri (Journal of Applied Geoscience and Engineering, 2025)
This study examines the geological conditions and slope stability of segments IG1 and IG2 in the Magazine access area of the Pani Gold Project, Pohuwato Regency. The research methods include geological mapping, scanline analysis, kinematic evaluation using stereonet, and Rock Mass Rating (RMR) and Slope Mass Rating (SMR) assessments. Segment IG1 consists of volcanic breccia with an RMR value of 57 (Class III, Fair Rock) and an SMR value of 45–50 (Poor), indicating wedge failure potential. Segment IG2 is dominated by dacite with an RMR of 60 (Class III, Fair Rock) and an SMR of 55–60 (Fair–Good), showing a tendency toward toppling failure. The results suggest that IG2 is relatively more stable than IG1, although localized failures may occur. Technical recommendations include slope reinforcement with rock bolts, shotcrete, and drainage systems to minimize slope failure risks.